2010
DOI: 10.1007/s10495-010-0496-6
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of NF-κB and activation of Nrf2 signaling by 1,2,4-triazine derivatives, protects neuron-like PC12 cells against apoptosis

Abstract: Oxidative stress has been implicated in the etiology of neurodegenerative diseases and aging. Indeed, accumulation of reactive oxygen species, such as hydrogen peroxide, generated by inflammatory cells, leads to oxidative stress, which may contribute to the neuronal degeneration observed in a wide variety of neurodegenerative disorders of the central nervous system, such as Alzheimer's disease. The present study indicates that H(2)O(2)-induced cell death can be inhibited in the presence of 1,2,4-triazine deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 49 publications
2
25
0
1
Order By: Relevance
“…However, this increase starts to decrease after a while [2,29]. To determine whether S. sahendica induces HO-1 or not, PC12 neurons were pretreated with 10, 25, 50 and 100 lg/ml of plant extract for 24 h and then exposed to H 2 O 2 .…”
Section: S Sahendica Treatment Resulted In Induction Of Ho-1 In Pc12mentioning
confidence: 99%
See 1 more Smart Citation
“…However, this increase starts to decrease after a while [2,29]. To determine whether S. sahendica induces HO-1 or not, PC12 neurons were pretreated with 10, 25, 50 and 100 lg/ml of plant extract for 24 h and then exposed to H 2 O 2 .…”
Section: S Sahendica Treatment Resulted In Induction Of Ho-1 In Pc12mentioning
confidence: 99%
“…Oxidative damage is mediated by reactive oxygen species (ROS) which are generated following cell lysis, oxidative burst or presence of excess free transition metals. Hydrogen peroxide (H 2 O 2 ), one of the main ROS, is produced during the redox process and has recently been considered as a messenger in intracellular signaling cascades which can cause lipid peroxidation and DNA damage, thus inducing apoptosis in many different cell types, including PC12 cells [2]. Therefore, therapeutic strategies aimed at preventing or delaying ROS-induced apoptosis might be a reasonable approach to treating AD.…”
Section: Introductionmentioning
confidence: 99%
“…evaluate the detailed mechanism of this cytoprotection, we previously examined antioxidant and antiglycating activities of these plants. The overexpression of antioxidant enzymes such as catalase and super oxide dismutase, as well as the reduction of lipid peroxidation and protein glycation, are the primary mechanisms of cell defense in oxidative stress conditions (Tusi et al 2010). In our previous study we confirmed that all of these mechanisms are triggered by Salvia species in cells exposed to H 2 O 2 (Asadi et al ).…”
Section: Procaspase-3mentioning
confidence: 99%
“…The inhibition of NF-kB translocation from the cytoplasm to the nucleus assumes a pivotal role in reducing uncontrolled oxidative and inflammatory reactions. Some evidences indicate that a cross talk between Nrf2 and NF-kB exists [58]. This is an important issue according to the relationship with the cascade of events triggered by some immunomodulators.…”
Section: Modulation Of Nrf2 and Nf-kbmentioning
confidence: 99%